Alleviating Financial Accounting Anxiety to Improve Academic Performance among Business Education Students in Colleges of Education in Nigeria - Aluko, Kudirat A.; Aishat, Aliyu; Adebayo, Fawale, Afiss; Mustapha, Aliyu Olanrewaju (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2026)
Despite its significance, a significant proportion of students encounter challenges when engaging with coursework involving calculations. As a result, the study examines the perceived influence of Financial Accounting Anxiety on the academic performance of business education students in colleges of education in Kwara State, Nigeria. The population comprised students across three (3) State-owned Colleges of Education, totalling 1,016, and the sample size was determined using Krejcie and Morgan's (1970) method, yielding 279. However, convenience sampling was used to distribute the questionnaire to relevant students. The data were obtained using a Google Forms questionnaire shared via WhatsApp among students. Descriptive and inferential statistical methods were employed to understand the data. A significant relationship was found between complex accounting standards and students' academic performance. Meanwhile, no significant effect of low self-efficacy on academic performance. An emotional response was found to be equally significantly related to the students’ academic performance. Finally, poor study habits were found to influence academic performance. The inherent involvement in accounting principles and standards often creates barriers to comprehension, thereby affecting students' ability to perform effectively in financial accounting courses. This suggests that the design and delivery of accounting curricula need to consider the cognitive load imposed by these standards and how they may exacerbate academic challenges for some students. Facilitators should endeavour to break down complex accounting methods into smaller, more digestible modules.